2024
DOI: 10.1002/advs.202401482
|View full text |Cite
|
Sign up to set email alerts
|

Photophore‐Anchored Molecular Switch for High‐Performance Nonvolatile Organic Memory Transistor

Syed Zahid Hassan,
Jieun Kwon,
Juhyeok Lee
et al.

Abstract: Over the past decade, molecular‐switch‐embedded memory devices, particularly field‐effect transistors (FETs), have gained significant interest. Molecular switches are integrated to regulate the resistance or current levels in FETs. Despite substantial efforts, realizing large memory window with a long retention time, a critical factor in memory device functionality, remains a challenge. This is due to the inability of an isomeric state of a molecular switch to serve as a stable deep trap state within the semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…The synthetic route for these diazirine‐based crosslinkers is depicted in Figure S1 (Supporting Information). In specific, an intermediate, 4‐[3‐(Trifluoromethyl)‐3H‐diazirin‐3‐yl]benzoic acid, was synthesized following the method described by Sakurai et al [ 33 , 34 ] and then coupled with ethylene glycol, 1,11‐undecanediol, and tetraethylene glycol to produce the crosslinkers CL‐C2, CL‐C11, and CL‐TEG, respectively. Thus, the three crosslinker variants, CL‐C2, CL‐C11, and CL‐TEG, share a common functional group, yet they exhibit variations in their bridge chain lengths.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthetic route for these diazirine‐based crosslinkers is depicted in Figure S1 (Supporting Information). In specific, an intermediate, 4‐[3‐(Trifluoromethyl)‐3H‐diazirin‐3‐yl]benzoic acid, was synthesized following the method described by Sakurai et al [ 33 , 34 ] and then coupled with ethylene glycol, 1,11‐undecanediol, and tetraethylene glycol to produce the crosslinkers CL‐C2, CL‐C11, and CL‐TEG, respectively. Thus, the three crosslinker variants, CL‐C2, CL‐C11, and CL‐TEG, share a common functional group, yet they exhibit variations in their bridge chain lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the HER rate observed in this study (564 µmol g −1 h −1 ) was somewhat lower than that reported in previous studies on F8BT, possibly owing to the presence of relatively low residual palladium content within F8BT nanoparticles (16 ppm, measured by inductively coupled plasma mass spectroscopy, ICP‐MS). [ 34 ] Furthermore, since the equivalent residual Pd in F8BT is the same as in each photocrosslinked photocatalysts, respectively, we speculated that the co‐catalytic effect of Pd would similarly influence the performance of each crosslinked F8BT nanoparticle. We also measured the performance of photocrosslinked F8BT nanoparticles over a wide range of optical wavelengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation